100% clean and renewable wind, water, and sunlight (WWS) all-sector energy roadmaps for the 50 United States1. Issue 7 (1st July 2015) - Jacobson, Mark Z.; Delucchi, Mark A.; Bazouin, Guillaume; Bauer, Zack A. F.; Heavey, Christa C.; Fisher, Emma; Morris, Sean B.; Piekutowski, Diniana J. Y.; Vencill, Taylor A.; Yeskoo, Tim W.
<x xml:space="preserve">Abstract</x> This paper presents roadmaps for each of the 50 United States to convert their energy infrastructures to 100% wind, water, and sunlight (WWS) for all purposes by 2050.